A new heterogeneous family of telomerically encoded Cryptosporidium proteins - Bouzid, Maha (Blackwell Publishing Ltd, 2013)
Cryptosporidiosis is predominantly caused by two closely related species of protozoan parasites the zoonotic Cryptosporidium parvum and anthroponotic Cryptosporidium hominis which diverge phenotypically in respect to host range and virulence. Using comparative genomics we identified two genes displaying overt heterogeneity between species. Although initial work suggested both were species specific, Cops-1 for C. parvum and Chos-1 for C. hominis, subsequent study identified an abridged ortholog of Cops-1 in C. hominis. Cops-1 and Chos-1 showed limited, but significant, similarity to each other and share common features: (i) telomeric location: Cops-1 is the last gene on chromosome 2, whilst Chos-1 is the first gene on chromosome 5, (ii) encode circa 50-kDa secreted proteins with isoelectric points above 10, (iii) are serine rich, and (iv) contain internal nucleotide repeats. Importantly, Cops-1 sequence contains specific SNPs with good discriminatory power useful epidemiologically. C. parvum-infected patient sera recognized a 50-kDa protein in antigen preparations of C. parvum but not C. hominis, consistent with Cops-1 being antigenic for patients. Interestingly, anti-Cops-1 monoclonal antibody (9E1) stained oocyst content and sporozoite surface of C. parvum only. This study provides a new example of protozoan telomeres as rapidly evolving contingency loci encoding putative virulence factors.